Electricity consumption, economic growth, urbanisation and trade nexus: empirical evidence from Iceland - Faisal, Faisal; Tursoy, Turgut; Gunsel Resatoglu, Nil; Berk, Niyazi (Economic Research-Ekonomska Istraživanja, 2018)
This study empirically investigates the relationship between economic growth, electricity consumption, trade and urbanisation in Iceland, covering the period 1965–2013. The A.R.D.L. bounds testing approach to co-integration is applied to investigate the existence of the long-run relationship. The causality was investigated among the variables using Granger causality under the V.E.C.M. framework. The A.R.D.L. bounds testing approach to co-integration confirms a long-run relationship between electricity consumption and its regressors. The empirical estimation indicates the existence of a positive and statistically significant impact of economic growth, trade and urbanisation on electricity consumption for Iceland, not only in the long-run, but also in the short-run. Furthermore, electricity consumption converges to its long-run position by 45.63% speed of adjustment using the channels of urbanisation, trade and economic growth. The results of Granger causality imply the presence of a feedback causal relationship between urbanisation and electricity consumption in the long-run, thus validating the feedback hypothesis. However, economic growth is causing trade, thus validating the growth-led trade hypothesis in the short-run. Additionally, no causal relationship was found between electricity usage and economic growth, which confirms the neutrality hypothesis. Implementing the energy conservation policy will have no damaging effect on economic growth for Iceland.